Assessment of Social Maturity among Adolescents in Bikaner, Rajasthan, India - , Manju Kanwar Rathore; Kusum, Shikha Kapoor (Archives of Current Research International, 2025)
Adolescence is the age of expressing mature behaviour in an individual. Being socially mature is the process of developing a satisfying relationship between a person and their surroundings. Adolescents from different cultural backgrounds may have different norms, values, and expectations for social behaviour, which may affect their social maturity and how they are perceived by others. The goal of the current study was to investigate the level of social maturity of adolescent students. The sample size consists of N=100 (50 boys, 50 girls), which had an equal number of both male and female adolescent students, also equally distributed in urban and rural areas, living in Bikaner city of Rajasthan state, India. A purposive sampling method was used to gather data for this study. An assessment of the chosen subjects' social maturity was conducted by using Dr. Nalini Rao’s Social Maturity Scale, whereas age, gender, residential area, family income and marital status, etc. taken as independent variables for the study. The data analysis was done by using suitable statistical methods, i.e. mean, standard deviation, frequency and percentage, etc. The overall data for total social maturity revealed that the majority of both males and females from rural and urban areas had a medium level of social maturity. All three subcomponents of the social maturity, i.e. Personal adequacy, Inter-personal adequacy and social adequacy, also had almost all the respondents account for a medium level of social maturity. In rural areas, 8.57 per cent of males and not a single female accounted for the low level of personal adequacy, while 85.71 per cent of males and 100 per cent of females had a medium level, and only 2 % of males had a low level of personal adequacy. In terms of inter-personal adequacy’s low level, 97.14 per cent of males and 98 per cent of females had a medium level, and 2.86 per cent of males and 2 per cent had a low level of inter-personal adequacy. Lastly, the majority of both males and females from rural and urban areas had a medium level of social maturity. So, in this study, almost all the respondents were better socially mature. Therefore, the study represented that the respondents were becoming socially mature. They should be placed in an appropriate setting and allowed to connect with their classmates for achieving a proper social maturity level at this stage of the life span.